2016
DOI: 10.1016/j.taap.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of aryl hydrocarbon receptor polymorphisms on TCDD-mediated CYP1B1 induction and IgM suppression by human B cells

Abstract: Previous studies have demonstrated that most of the intraspecies variation in sensitivity to the toxic effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), including suppression of antibody responses, in murine models is due to single nucleotide polymorphisms (SNPs) within the aryl hydrocarbon receptor (AhR) gene. The underlying reason for variation in sensitivity to TCDD-induced suppression of IgM responses among humans is not well understood, but is thought, in part, to be a result of different polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…A second interesting phenomenon that we and others have described in B cells is that AHR activation must occur within the first 24 h post B cell activation to induce suppression of the IgM response (Kovalova et al, 2016a). The temporal relationship between AHR activation and the activation of the B cell suggests Figure 4.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A second interesting phenomenon that we and others have described in B cells is that AHR activation must occur within the first 24 h post B cell activation to induce suppression of the IgM response (Kovalova et al, 2016a). The temporal relationship between AHR activation and the activation of the B cell suggests Figure 4.…”
Section: Discussionmentioning
confidence: 84%
“…Murine studies have shown that suppression of the IgM response by AHR ligands is closely linked to a decrease in mRNA levels for the immunoglobulin chains (IgH, IgJ, and Igj chains) (Schneider et al, 2008). Previous studies have also demonstrated that AHR activation impairs IgM responses by human B cells to a variety of stimuli including: PWM; co-stimulation by CD40L with cytokines; and toxic shock syndrome toxin superantigen (Kovalova et al, 2016a;Lu et al, 2011;Phadnis-Moghe et al, 2015;Wood and Holsapple, 1993). It has been broadly assumed that the molecular mechanisms responsible for immune suppression by AHR ligands, including suppression of the IgM antibody response, would be similar across animal species.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites 2019, 9, exposure, the host would have a dampened inflammatory response, due to the immature B cells. It was also noted that the major window for TCDD and AHR to affect B cells is 12 h after stimulation [29,32]. This is important because if there a sub-chronic exposure of TCDD, the B cells would be affected throughout the exposure, and when the exposure stopped there is a possibility of a buildup of LPS that was not cleared by the delayed B cells.…”
Section: Modulation Of Bacterial Pathways After Tcdf Exposurementioning
confidence: 99%
“…Studies in mouse, rat and human B lymphocytes show similar levels both in terms of the magnitude of TCDD-induced IgM suppression as well as similarity in time-of–addition kinetics (Kovalova et al, 2016). Concordance across all three animal species suggested a common mode of action.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the window of sensitivity during which TCDD can suppress IgM secretion is similar between mouse, human and rat B cells, suggesting a common mechanism of action of IgM suppression. Specifically, TCDD must be added to the activated B cells within the initial 12 h post-stimulation to suppress IgM secretion (Dooley and Holsapple, 1988; Sulentic et al ., 1998; Kovalova et al ., 2016). The relatively narrow window of sensitivity suggests TCDD-mediated interference with a critical event shortly following B-cell activation.…”
Section: Introductionmentioning
confidence: 99%